BAKTI SOSIAL RAMADHAN DAN PENDAMPINGAN WIRAUSAHA KEPADA WARGA SEBAGAI UPAYA MENUMBUHKAN KECERDASAN SPIRITUAL - Nugroho, Arif Julianto Sri; Haris, Abdul; Tukiyo; Prasetyo, Jarot; Setyawanti, Dandang; Herawati, Nanik; Unigowati, Dwi Wahyuni; Murjito, Winarno Heru; Nugrahani, Cahaya (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2024)
As students and lecturers in higher education, what we can do is to contribute back to society. We need to apply the rules of SQ, empathy, entrepreneurship, and give and take in The Ramadhan 2024. We believe that even though we are not giving them much, but it is better than no right. It may sound like there is no innovation, but we do admit that. However, we thought that the outcome we get is far more important than Spiritual Quotient and entrepreneurship innovation we did not even have any ideas about entrepreneurship and empathy in the Muslim spirit during the Ramadhan 2024  for the faculty of economics and psychology students.